Knowledge, attitudes, and food safety risk perception towards microplastics in Sardinella lemuru (tamban) of the consuming population in Cebu, Philippines and their willingness to follow food safety policies in the control of microplastics in food - Degamo, Eir-Roumar Lowell I.; Asst. Prof. Rustia, Abigail S. (Quezon City University of the Philippines Diliman, 2023)
No policies regulating microplastics in food in the Philippines have been implemented despite the growing food safety risks imposed by the increasing microplastic concentration in the environment. This study evaluated the influence of knowledge, attitude, and food safety risk perception of consumers from Cebu, Philippines towards microplastics in Sardinella lemuru (tamban) and their willingness to follow food safety policies relevant to the control of microplastics in food. To meet the general objective, the following specific objectives were conducted: (1) development of a survey tool for the evaluation of food safety risk perception of microplastics in S. lemuru (tamban) by the consuming population in Cebu, Philippines; (2) establishment of baseline information on the influences of knowledge and attitude towards risk perception of microplastics in S. lemuru (tamban) by the consuming population in Cebu, Philippines; and, (3) establishment of the willingness of the consuming population of Cebu, Philippines to follow food safety policies to control microplastics in food. An online survey form, consisting of 15 questions on Knowledge, 14 on Attitudes and Behavior, 11 on Risk Perception, and 7 questions on the Willingness on the Reduction of Microplastic Emissions, was developed and used to gather responses from 40 consumers of S. lemuru in Cebu, Philippines. Partial least squares structural equation modeling (PLS-SEM) analysis was used in the developed Degamo & Rustia exploratory PLS-SEM model (Figure 8) and showed a path coefficient of 0.357 between Knowledge and Risk Perception indicating that risk perception is significantly affected by the knowledge of the consuming population. The analysis also showed a path coefficient of 0.187 between Personal Willingness and Public Willingness indicating that willingness of the consuming population to follow policies is significantly affected by their personal willingness to lessen microplastic production. The practical implications of results on Knowledge, Attitude and Behavior Towards Microplastics, Risk Perception, Public Willingness, and Personal Willingness suggested that policies formulated and implemented should consider the stated variables in the government program such as incentives and social media drives.
Thesis
Includes bibliographical references (pages 98-129)
Keywords: Microplastics -- Philippines; Food handling -- Law and legislation -- Philippines; Consumers -- Attitudes; Consumer behavior -- Cebu Island (Philippines).; Sardinella lemuru -- Cebu Island (Philippines).